Enteric viral infections as potential risk factors for intussusception - Mansour, Adel M; El Koutby, Montasser; El Barbary, Mohamed M; Mohamed, Wissam; Shehata, Sameh; El Mohammady, Hanan; Mostafa, Manal; Riddle, Mark S; Sebeny, Peter J; Young, Sylvia Y.N.; Abdel-Messih, Ibrahim (The Journal of Infection in Developing Countries, 2013)
Introduction: We aimed to identify potential risk factors for intussusception (ISS) among children presenting to two pediatric hospitals in Egypt. Methodology: In this case-control study, enrolled children < 3 years old with ISS (confirmed radiologically and/or surgically) were matched by age and gender to controls admitted with acute non-abdominal surgical illnesses. Stool samples were collected and tested for various enteric bacteria, rotavirus, enteric adenoviruses (EA, 40 and 41) and astroviruses using commercially available ELISA diagnostic kits. Results: From December 2004 to May 2009, 158 cases and 425 matched controls were enrolled. A history of diarrhoea and cough over the preceding four weeks of interview were more common in cases than controls, respectively. Children with mothers who had secondary education and above were 2.2 times more likely to have ISS than those whose mothers had a lower level of education. In spite of the low detection rate of EA infection (regardless of diarrhoea history) and asymptomatic rotavirus infection, they were detected in higher frequencies in cases than controls; however, infection with astrovirus and bacterial pathogens did not appear to be associated with increased risk of ISS. Conclusions: History of diarrhoea and cough over the four weeks preceding the study and maternal education above secondary level were potential risk factors for ISS. EA and asymptomatic rotavirus infection were detected in higher frequencies among cases than controls; however, association with ISS cannot be confirmed. Additional research is needed to confirm these findings and evaluate the pathogenesis which may link such infections with ISS.